PENGARUH TINGKAT LIKUIDITAS, TINGKAT LEVERAGE DAN TINGKAT PROFITABILITAS TERHADAP KELENGKAPAN PENGUNGKAPAN DALAM LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mario Dwisaktris; Marini Purwanto; Sofian Sofian (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2023)
This study seeks to examine the effect of liquidity, leverage and profitability on the completeness of disclosures. This research was done using a quantitative method and hypothesis testing using multiple linear regression as a data analysis technique. This research used a purposive sampling method using manufacturing public companies listed on the Indonesia Stock Exchange in the year of 2019-2020 as a population. After reducing the data, 108 sample companies were obtained, totaling 216 data. This research found out that profitability has no effect on the Completeness of Disclosure of the Company's Financial Statements while liquidity and leverage affect the Completeness of Disclosure of the Company's Financial Statements.